Management of bladder cancer in the elderly: clinical decision-making and guideline recommendations. (October 2010) - Shalhoub, Philip J; Quek, Marcus L
Evaluation of: Bolenz C, Ho R, Nuss GR et al. : Management of elderly patients with urothelial carcinoma of the bladder: guideline concordance and predictors of overall survival. BJU Int. (2010) (Epub ahead of print). Treatment recommendations for all stages of bladder cancer have been proposed in the form of clinical guidelines from the European Association of Urology and the American Urological Association. However, the therapeutic considerations, especially when dealing with elderly patients with limited functional status and associated comorbidities, may be much more complex. This retrospective study reviewed the records of 206 patients aged over 75 years with bladder cancer and compared their subsequent treatment with established European Association of Urology and American Urological Association guidelines to see if their actual treatment was concordant or discordant with the published recommendations. Overall guideline concordance was relatively high (88.8%) at this tertiary referral institution. While treatment of muscle-invasive bladder cancer in the elderly can be performed in accordance with accepted guidelines, the margin of error is greatly reduced and proper patient selection and attention to detail is critical to ensure a favorable outcome. Further research is needed to more objectively distinguish patients who may benefit from aggressive cancer therapy from those with serious competing risks who would probably die from other causes.